The Census of Population, 1946 - Lyon, Stanley (Statistical and Social Inquiry Society of Ireland, 1947)
At decennial intervals a Census of Population of Ireland (since 1922 the Twenty-Six Counties of Eire) is normally taken. Census date 1946 has been fixed by Order for Sunday, 12th May. A conference was held of representatives of the Public Departments which had sent in suggestions, and after detail discussion on the various suggestions put forward, a draft schedule was drawn up which, with some minor alterations, was submitted to the Minister for Industry and Commerce for approval. The pattern of the Census schedule to be used on this occasion differs considerably from those used for former Irish Censuses.
Read on Thursday, 25th April, 1946
Keywords: Irish census 1946; Population count; Census procedures; 314.15